Human Cytomegalovirus infection in the era of vaccine development: case series of immunocompromised patients - Marascio, Nadia; Pavia, Grazia; Mazzei, Chiara; Pantanella, Marta; Giorgio, Emanuele; Manno, Michele; Gigliotti, Simona; Barreca, Giorgio Settimo; Peronace, Cinzia; Matera, Giovanni; Quirino, Angela (Frontiers in Virology, 2025)
IntroductionHuman Cytomegalovirus (CMV) infection represents a significant health burden, particularly for immunocompromised patients, including solid-organ transplant (SOT) recipients and people living with human immunodeficiency virus (PLWH). Despite the availability of antiviral prophylaxis and treatment, prolonged therapy can lead to viral drug resistance, complicating disease management. In this study, we present a series of CMV cases in immunocompromised patients, including two SOT recipients and one PLWH patient, focusing on microbiological data, clinical presentation, and therapeutic management.MethodsCMV serostatus and DNA viral load were carried out by Chemiluminescence Immunoassay (CLIA) and quantitative real-time PCR to monitor patient follow-up.ResultsThe three patients had CMV reactivation following an immunocompromised status. The prompted antiviral treatments determined the viral infection resolution, despite CMV-related complications worsening clinical outcomes.DiscussionThe development of a safe and effective CMV vaccine represents a needed challenge, especially for individuals at high risk of severe CMV-related complications. However, it is difficult to achieve high CMV variability. Our findings contribute to the ongoing discussion on the importance of developing vaccines to mitigate CMV-related morbidity in vulnerable populations.